Lygia Bojunga: imagens da escrita - Passos, Vanessa Paulino Venancio (2021)
This research comprises an investigation, from the autobiographical and metalinguistic works of Lygia Bojunga (1932-), about her process of literary creation to fictional creation. Therefore, we built an analytical and interpretive path in order to think, not only about the trajectory of a writer, but also about the relationship between word and image, considering that the author's creative process is related to the image, as well as with other arts such as painting and theatre. Furthermore, our interest was concentrated in the process of making each book written by Lygia Bojunga, specifically and in relation to the set of her work with a comparative bias. We seek to observe and explain how Bojungian literature achieves a complexity when relating to categories such as: autobiography, painting, the unconscious and the theater, in order to reach significant dimensions, guided by in-depth understandings of "life and work" and “autobiography”, as expressed by Dominique Maingueneau and Philippe Lejeune. Therefore, the research proposes the analysis of Lygia Bojunga's written images, based, in particular, on the theoretical assumptions of Dominique Maingueneau (1995), Philippe Lejeune (2014), Paul Ricoeur (2007), Fayga Ostrower (2013) and Carl Jung (2017).